2022
DOI: 10.1097/jom.0000000000002536
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preference and Frequency of Teleworking with Work Functioning Impairment

Abstract: Objective: We examined whether teleworking preference and frequency were associated with work functioning impairment. Methods: This online cross-sectional study was conducted using a self-administered questionnaire among 27,036 full-time Japanese workers. The Work Functioning Impairment Scale was used to measure work functioning impairment, and we performed multilevel logistic regression analysis Results: Higher odds ratios for work functioning impairment were observed among employees who preferred to telework… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…There are several factors that appear to modulate the relationship between the frequency of telework and loneliness. One is preference for telework, which affects mental health more strongly than the frequency of telework [ 29 , 30 ]. For instance, people who prefer to work from home are less stressed, and stress and loneliness are strongly correlated [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several factors that appear to modulate the relationship between the frequency of telework and loneliness. One is preference for telework, which affects mental health more strongly than the frequency of telework [ 29 , 30 ]. For instance, people who prefer to work from home are less stressed, and stress and loneliness are strongly correlated [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The review findings suggest that there is a potential for continual teleworking in terms of self-reported performance and organizational economic performance indicators, which could be obtained from the best combinations of different flexible working arrangements. For instance, Yamashita et al ( 2022 ) observed impaired work functioning among employees who preferred and teleworked four or more days a week compared with those who almost never teleworked. Although this review did not investigate closely the topic of frequency or intensity and preference for telework, it would be interesting to study whether frequency/intensity of telework in relation to preference for it has any significance for organizational performance.…”
Section: Discussionmentioning
confidence: 99%
“…The secondary and tertiary outcomes were work functioning impairment and reduced work participation, separately, as cause-specific outcomes. Work functioning impairment was defined as a score of 21 or higher on the Work Functioning Impairment Scale (WFun), based on the cutoff point to detect the occurrence of presenteeism in previous studies 22,38,39 . The WFun was developed and validated to measure work function impairment according to the Consensus-based Standards for the Selection of Health Measurement Instruments 40 .…”
Section: Methodsmentioning
confidence: 99%
“…Covariates at the baseline included age (four quintile), sex (binomial), educational attainment (college graduate or higher), marital status (married, unmarried, or widowed/separated), 22 having children (binomial 14 ), smoking habits (never, past, current), drinking habits (never, past, current), and having more than one underlying diseases (binomial) from hypertension, diabetes, asthma, bronchitis/pneumonia, atopic dermatitis, periodontitis, angina pectoris, cardiac infarction, cerebral vascular disease, chronic obstructive pulmonary disease, malignancy, chronic back pain, depression, and any other psychiatric disease 41 . Equivalent household income (four quintile 42 ), employment status (employer and self-employed, regular employee, others including nonregular employee), fear of Coronavirus-2019 Scale (FCV-19; four quintile), and mean effective reproduction number of COVID-19 in the month before the survey were considered for each prefecture as time-varying covariates 43,44 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation